Investigation on the friction stir assisted lap joining of pure copper and aluminium 6063 alloy. (2022) - Prakash, Om; Dwivedi, Suryank; Pagrut, Shravan; Singh Rajawat, Manvendra; Raj, Ratnesh; Kumar Srivastava, Ashish; Rai Dixit, Amit
Abstract: Among solid-state joining processes, the friction stir welding process stands out for its ability to fabricate specimens with desired thickness and high-quality bonding of the specimens without melting and solidification. In the present work, two dissimilar materials with distinct thermomechanical behavior, such as AA6063 alloy and pure Cu, were used to fabricate the laminated joint through the friction stir welding process (FSW). The FSW was employed to achieve high linear weld density, microstructural, and mechanical analysis of the fabricated samples. The linear weld density results show that the sample was formed with high weld density. A microstructural and EDX study confirms the mixing and purity of both materials in the joining area. Moreover, microscopic analyses of the weld or stir zone were employed to analyze the joint quality in terms of linear weld density and tunneling defects. The Micro-hardness test also showed an improvement in the micro-hardness value at both base materials and stir zone regions. The obtained results show the FSW can fabricate the dissimilar laminate with improved microstructural and mechanical properties.